Comparing the intraoperative complication rate of femtosecond laser-assisted cataract surgery to traditional phacoemulsification - Ming Chen; Christian Swinney; Mindy Chen (International Journal of Ophthalmology, 2015)
AIM: To compare the complication rate of femtosecond laser-assisted cataract surgery (FLACS) and traditional phacoemulsification for the first 18mo of FLACS use at a private surgical center in Hawaii. METHODS: A retrospective chart review was conducted from January 2012 to June 2013. The first 273 consecutive eyes receiving FLACS and 553 eyes receiving traditional phacoemulsification were examined. All surgeries were performed at a single surgical center in Hawaii. The presence of intraoperative complications was used as the main outcome measure. Approval was obtained from the institutional review board of the University of Hawaii. RESULTS: The overall complication rate for FLACS was 1.8%, while that of the traditional procedure was 5.8% (P<0.05). A majority of the surgeons (80%) had a lower complication rate while using FLACS. CONCLUSION: FLACS is comparable in safety, if not safer, than traditional cataract surgery when performed by qualified cataract surgeons on carefully selected patients.